URGENSI PENDIDIKAN ANAK USIA DINI (PAUD); SEKARANG DAN MASA DEPAN - Sumiyati . (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2012)
The notion that education can be only begun after the age of primary school, it is not true. Even education is started to childhood, actually it has been already too late. To remember the importance of childhood were often termed the golden age, then it is needed an education or an agency can help to grow and develop all the potential of a child. Namely, an institute for early childhood education that can facilitate needs is needed by the child needs to optimize their potential by using good methods. In addition, it is also needed of thinkers who are able to create an Early Childhood Education institution in the future with good quality, and using Quality integrated Management (MMT) / Total Quality Management (TQM).